GABC: A comprehensive resource and Genome Atlas for Breast Cancer. Issue 4 (31st October 2020) - Zhang, Yunpeng; Wang, Peng; Li, Xin; Ning, Shangwei; Li, Xia; Cao, Yan; Chen, Steven Xi
Abstract: We developed the Genome Atlas of Breast Cancer (GABC), a global map of noncoding events in the human genome associated with breast cancer that provides a valuable reference resource for users to investigate the underlying genome abnormalities in breast cancer patients. Although significant progress has been made in breast cancer treatment, its morbidity and recurrence rates in women are still high worldwide. Curation and integration of breast cancer‐related dysregulations from multiple aspects is essential for disease prevention and diagnosis. In this study, we developed the GABC, which contains 10 172 aberrant noncoding events occurring at multiomics levels, including the genome (single nucleotide polymorphism and somatic mutation), transcriptome (long noncoding RNA and microRNA) and epigenome (DNA methylation, enhancer and superenhancer). Each event entry provides descriptions of detailed biological mechanisms specific to the region or element. Users can also check the genome locations and relationships of functional regulators. The GABC provides a flexible and user‐friendly interface for users to search, browse and download data. In addition, the GABC provides an interface to submit newly discovered noncoding events that can be included in the database. Therefore, the GABC aims to constantly enhance our understanding of noncoding genomic events in breast cancer. Abstract : What's new? Breast cancer is a heterogeneous and complex disease associated with changes in the genome, transcriptome, and epigenome, including in non‐coding regions. However, public resources that focus on non‐coding regions and multi‐omics aspects of breast cancer are still limited. Here, the authors present the Genome Atlas of Breast Cancer (GABC), which contains 10, 172 aberrant non‐coding events occurring at the genome (SNP and somatic mutation), transcriptome (lncRNA and miRNA), and epigenome (DNA methylation, enhancer, and super‐enhancer) levels. The GABC provides a user‐friendly multi‐omics interface to search, browse, and download data to better understand the role of non‐coding genomic events in breast cancer.